Constraints Analysis of Wheat Growers of Intermediate Zone of Jammu Region - Manhas, Jasbir Singh; Kher, S. K.; Kumar, Parveen (Indian Journal of Extension Education, 2018)
The present study was conducted in purposively selected Rajouri district of Jammu and Kashmir to find out the constraints  in the adoption of recommended wheat production technology. There are 9 blocks in Rajouri district, out of which one  block namely Rajouri was selected on the basis of maximum area under wheat cultivation. From Rajouri block, ten  villages were selected on the basis of maximum area under wheat cultivation. From each selected village, 12 tribal and 12  non-tribal wheat growers were selected randomly. Thus in all, 240 farmers (120 tribal and 120 non-tribal farmers) were  included in the sample of the study. The analysis of information collected by personal interview method revealed that  50.00 per cent of respondents had medium level of constraints, whereas 26 per cent and 24 per cent of respondents had low  and high levels of constraints respectively regarding adoption of recommended wheat production technology. The  calculated z-value was greater than its tabulated value at 1 percent level of significance. It means that there was a  significant difference between tribal and non-tribal farmers with respect to constraints faced by them in adoption of  recommended wheat production technology. Age, education, size of land holding, extension personnel contact,  participation in extension programme, mass media exposure and socio-economic status of the respondents were found to  be positive and significantly correlated with constraints faced by the wheat growers.
Keywords: Analysis; constraints; wheat growers